P037 USP16-mediated deubiquitination of calcineurin A controls peripheral T cells maintenance and attenuates intestinal inflammation. (25th January 2019) - Zhang, Y; Liu, R; Fan, K; Huang, L; Gao, Z; Huang, T; Zhong, J; Mao, X; Mao, X; Wang, F; Xiao, P; Zhao, Y; et al.
Abstract: Background: T cells play important roles in the pathogenesis of inflammatory bowel diseases (IBD). And ubiquitination and deubiquitination are important epigenetic modifications in immune responses. The process of how USP16 (ubiquitin carboxyl-terminal hydrolase 16) regulates the intestinal inflammation has never been explored. Methods: USP16 expression in isolated PBMCs and intestinal tissues of IBD patients and healthy controls were examined by quantitative real-time PCR (qRT-PCR) and immunohistochemistry respectively. T-cell-specific USP16 knockout mouse was generated with the Cre/LoxP technology. Colitis was induced in Rag1−/− mice by transfer of CD4+CD25-CD45RBhi T cells from C57/Bl6 or transgenic mice. T cells were isolated from mice, and the T-cell characteristics were analysed by flow cytometry and qRT-PCR. We used western blot and calcium flux to seek for the substrate of USP16, and immunoprecipitation and immunofluorescence were used to confirm the interaction. Plasmid transfection to the HEK293T cells and mass spectrometry were used to find the ubiquitinated point on the substrate. Results: IBD patients and inflamed intestinal tissues have higher levels of USP16 than controls. T-cell-specific USP16-knockout mice exhibited less severe colitis and less CD4+ T cells infiltration than the C57/Bl6 mice. USP16-deficient T cells had homeostasis dysregulation, impaired proliferation, defected differentiation, and normal migration ability. The calcium-triggered deubiquitination of calcineurin A (CNA), encoded by Ppp3cb or Ppp3cc, in a manner consistent with these defects. We found that the CNA is constitutively ubiquitinated on lysine 327 and that the resulting polyubiquitin chain is rapidly removed by USP16 in response to intracellular calcium stimulation. The K29-linked ubiquitination of CNA impaired NFAT recruitment and the transcription of NFAT-targeted genes. Conclusions: Our work elucidates the physiological function of calcineurin ubiquitination and its deubiquitinase USP16 in peripheral T cells. Notably, our results provide a critical mechanism for the regulation of calcineurin activity and a novel immunosuppressive drug target for the treatment of IBD.